Experimental and Computational Studies on N-alkylation Reaction of N-Benzoyl 5-(Aminomethyl)Tetrazole - Younas Aouine; Aaziz Jmiai; Anouar Alami; Abdallah El Asri; Souad El Issami; Idriss Bakas (Chemistry, 2021)
The N-alkylation reaction of N-benzoyl 5-(aminomethyl)tetrazole (5-AMT) with benzyl bromide was carried out in the presence of K2CO3 as a base. Two separable regioisomers were obtained, thus their purification led to determine the proportion of each of them, and their structures were attributed essentially based on 1H and 13C NMR spectroscopy in addition to the elemental analysis and MS data. In order to confirm the results obtained at the synthesis level, a computational study was carried out by application of density functional theory (DFT) using the Becke three-parameter hybrid exchange functional and the Lee-Yang-Parr correlation functional (B3LYP).